Investigation of the risks associated with the prolonged use of hormonal contraceptives in women residents of the Metropolitan Region of Belém - PA (Research, Society and Development, 2021)
Introduction: Genetic and environmental diseases such as thrombogenic mutations, thrombophilia in pregnancy, venous thromboembolism, migraine with aura, nausea, headache, diabetes, hypertension, obesity, breast cancer, aneurysm and glaucoma can be caused by the prolonged use of contraceptives. Objective: To analyze the risks associated with the prolonged use of contraceptives and adverse reactions in women living in the Metropolitan Region of Belém, PA. Methodology: A descriptive qualitative and quantitative study was developed, carried out through an online epidemiological questionnaire, with open and closed questions, to carry out the pharmacoepidemiological profile of the users prepared in Google Forms and disseminated on social networks. Results: 234 questionnaires, in which 19 were excluded, a total of 215 questionnaires answered by users of hormonal contraceptives, with the analysis of profiles, characteristics, guidance on the use of methods and adverse reactions: weight gain, appearance of pimples, swollen breasts and soreness, headache and nausea, mood swings and menstrual flow, leg pain and swelling, and migraine with aura. Conclusion: There was a presence of risks linked to genetic and environmental factors and adverse reactions associated with the prolonged use of hormonal contraceptives, making it evident the need for medical guidance and hormonal tests before adherence and choice of hormonal contraceptive method, being essential for effectiveness control of pregnancy and health of users of hormonal contraceptives in the RMB.